Exploring Cultural Differences in Expressive Suppression and Emotion Recognition. (May 2018) - Sun, Michael; Lau, Anna S.
Previous research has shown that the habit of suppressing emotional expressions is associated with long-term, general reductions in social cognitive abilities and interpersonal adjustment. This may be because theoretically, habitual suppression requires the fixation of attention to the self instead of to others. The present research explored the association between the habitual tendency to suppress one's own emotions and accuracy in recognizing the emotions of others. Emotion recognition accuracy was tested across two tasks, a limited-channel task that presents limited emotional information and a multimodal full-channel task. We further explored cultural differences in this association given that expressive suppression may be normative for individuals of Asian descent due to cultural motivations toward social harmony and interdependence. Our findings revealed few cultural group differences. U.S.-born Asian Americans outperformed foreign-born Asian Americans and European Americans in limited-channel emotion recognition. However, the three groups did not differ in terms of interdependent self-construal, habitual emotion suppression, and full-channel emotion recognition ability. Interdependent self-construal was related to greater habitual suppression and emotion recognition accuracy in the full-channel task. Habitual emotion suppression was negatively related to limited-channel but not full-channel emotion recognition. There was no evidence of cultural differences in the link between habitual suppression and emotion recognition.